Rancangan Manajemen Proyek Komputer Pada PT Lovalattes Indonesia - Agung Wijoyo; Ahmad Fajri; Moh. Ridzki Alif Maulana; Nazila Iva Sugianisa; Rio Ardy Milala (CV. Multi Kreasi Media, 2022)
Role technology in solving all difficulties is demanded by the progress of the times, human desire for high work problems,and information technology. Electronic commerce, sometimes known as